Mitochondrial uncoupling proteins and energy metabolism - Busiello, Rosa A.; Savarese, Sabrina; Lombardi, Assunta (Frontiers in Physiology, 2015)
Understanding the metabolic factors that contribute to energy metabolism (EM) is critical for the development of new treatments for obesity and related diseases. Mitochondrial oxidative phosphorylation is not perfectly coupled to ATP synthesis, and the process of proton-leak plays a crucial role. Proton-leak accounts for a significant part of the resting metabolic rate and therefore enhancement of this process represents a potential target for obesity treatment. Since their discovery, uncoupling proteins have stimulated great interest due to their involvement in mitochondrial-inducible proton-leak. Despite the widely accepted uncoupling/thermogenic effect of uncoupling protein one (UCP1), which was the first in this family to be discovered, the reactions catalyzed by its homologue UCP3 and the physiological role remain under debate. This review provides an overview of the role played by UCP1 and UCP3 in mitochondrial uncoupling/functionality as well as EM and suggests that they are a potential therapeutic target for treating obesity and its related diseases such as type II diabetes mellitus.